Group Emotion Regulation Therapy for Illness Anxiety Disorder: A Randomized Controlled Trial - Arash Aghighi; Nurallah Mohammadi; Changiz Rahimi Taghanaki; Mahdi Imani (Fasa University of Medical Sciences, 2021)
Background & Objective: People with Illness Anxiety Disorder experience excessive worry and in this regard, they have a lot in common with Generalized Anxiety Disorder. Emotion Regulation Therapy (ERT) is a multifaceted and integrated treatment that is widely used for Generalized Anxiety Disorder and its effectiveness in anxious factors has been established in many studies. The aim of the present study is to examine Effectiveness of Emotion Regulation Group Therapy in symptom reduction and worry in individuals with Illness Anxiety Disorder through a Randomized Clinical Trial (RCT). Materials & Methods: This is a Randomized Clinical Trial (RCT) experimental study with pre-test and post-test and control group. Population of the of the present study included all people with Illness Anxiety Disorder in Shiraz in 2019 who went to the psychiatric clinics of Shiraz University of Medical Sciences. The sample was 16 people with Illness Anxiety Disorder who were randomly assigned to the experimental group and the control group. The subjects in the experimental group and the control group were assessed in both pre-test and post-test periods using Structured Clinical Interview for DSM-5 (SCID-5-5), Anxiety and Related Disorders Interview Schedule for DSM-5 (ADIS-5) and The Penn State Worry Questionnaire (PSWQ). Results: Results showed that group format of emotion regulation therapy significantly improved symptoms of anxiety and worry of individuals with illness anxiety disorder. Conclusion: Emotion Regulation Therapy throughout intervention in worry and emotion regulation construct which is known as mediators in the treatment of many disorders, significantly improve symptoms and worry of people with Illness Anxiety Disorder.